2007
DOI: 10.1111/j.1440-1746.2007.04844.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of vitamin K on recurrent disease in patients with hepatocellular carcinoma arising from hepatitis C viral infection

Abstract: Vitamin K2 may have a suppressive effect on the recurrence of HCC and a beneficial effect on tumor recurrence. However, there was no significant difference in the survival rates. The chemopreventive effects of vitamin K2 are not sufficient. The development of a further regimen such as combination therapy is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 18 publications
0
50
0
Order By: Relevance
“…Recently, sorafenib was tested for prevention of recurrence after curative therapy, including resection and ablation (the STORM study), but again no benefits to recurrence-free survival were observed [127] . A Japanese group previously showed positive effects of acyclic retinoids and vitamin K analogues on recurrence-free survival, but overall survival was not improved and large-scale studies were not performed appropriately [128,129] . Interferon has been suggested as an adjuvant therapy after resection [130] .…”
Section: Adjuvant Therapy After Resectionmentioning
confidence: 99%
“…Recently, sorafenib was tested for prevention of recurrence after curative therapy, including resection and ablation (the STORM study), but again no benefits to recurrence-free survival were observed [127] . A Japanese group previously showed positive effects of acyclic retinoids and vitamin K analogues on recurrence-free survival, but overall survival was not improved and large-scale studies were not performed appropriately [128,129] . Interferon has been suggested as an adjuvant therapy after resection [130] .…”
Section: Adjuvant Therapy After Resectionmentioning
confidence: 99%
“…YAC-1 cells (2x10 6 ) were labeled with 3.7 MBq of Na 2 51 CrO 5 (MP Biomedicals, Irvine, CA) at 37˚C for 1 h in a shaking water bath. Labeled target cells were washed with PBS and adjusted to 1x10 5 /ml in a complete medium, then seeded at a concentration of 1x10 4 cells/well in micro-well plates. The effector cells (lymphocytes) were added to the wells at effector to target (E:T) ratios of 100:1, 50:1, and 25:1 in a total volume of 200 μl.…”
Section: Animalsmentioning
confidence: 99%
“…Most patients with HCC also suffer from liver cirrhosis, which is the major risk factor for HCC, mainly caused by infection with either the hepatitis B virus (HBV) or the hepatitis C virus (HCV) (2). Ursodeoxycholic acid (3) and glycyrrhizin (4) have been reported to be effective in preventing liver carcinogenesis, while recently the preventive effects of vitamin K2 (5) and acyclic retinoid (6) towards recurrence in patients with HCC have been reported. Nevertheless, HCCs frequently occur in patients with HCV cirrhosis at an annual rate of ~8% in Japan, with recurrence within 5 years seen in 70% of cases (7).…”
Section: Introductionmentioning
confidence: 99%
“…46 The use of menaquinone in the treatment of hepatocellular carcinoma (HCC) has been investigated by a number of level 2 RCTs. [47][48][49][50][51][52][53][54][55] Two small trials examined the ability of menaquinone (MK-4, 45 mg/day) to suppress the development of HCC in patients with hepatitis C. 54,55 Both studies observed a lower proportion of patients develop HCC with menaquinone treatment; however, this effect was statistically significant in only one study. 54,55 Several RCTs have evaluated the effect of menaquinone (MK-4, 45 mg/day) in reducing recurrence and mortality after surgical or ablative treatment of HCC.…”
Section: Clinical Impact On Cancermentioning
confidence: 99%